Monetary Policy Dynamics and Macroeconomic Stability: A Post-Pandemic Empirical Study in Indonesia - Sukma Hendrian (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
The COVID-19 pandemic has caused a significant shock to global economic stability, including Indonesia, through growth contractions, soaring inflation, and exchange rate volatility. This research aims to analyze the dynamics of monetary policy and its influence on Indonesia's macroeconomic stability in the post-pandemic period. Using a qualitative approach through in-depth interviews, questionnaires to 120 licensed employees in the financial sector, as well as observations of macroeconomic indicators, the study yielded several important findings. First, monetary policy, especially the adjustment of the benchmark interest rate (BI7DRR), has proven effective in suppressing inflation from 5.5% in 2022 to 3.2% in 2023, while maintaining the stability of the rupiah exchange rate in the range of Rp14,800-Rp15,500 per USD. Second, the results of the questionnaire showed that 73% of respondents considered monetary policy effective in controlling inflation and 81% considered the exchange rate stable, but only 62% of respondents assessed that the policy encouraged MSME credit recovery. Third, the results of the interviews emphasized the importance of coordinating monetary and fiscal policies, especially in energy and food price controls, to support short- and medium-term stability. These findings confirm that while monetary policy plays an important role in maintaining macro stability, its limitations to real sector recovery demand cross-policy synergy. This research provides an academic contribution in the form of integration of empirical data and practitioner perceptions, as well as practical implications for the formulation of adaptive, collaborative, and inclusive monetary strategies in the midst of post-pandemic global dynamics.